Learning and Teaching Geological Field Skills in a Virtual World: Insights From an Undergraduate Virtual Fieldtrip in Kinlochleven, Scotland - Matthew J. Genge; Valentin Laurent; Philippa J. Mason; Alan R. T. Spencer; Mark D. Sutton; Alex C. Whittaker (Earth Science, Systems and Society)
Virtual fieldtrips enable the teaching of field geology remotely or in classroom-settings by leveraging video-game technologies. We describe the development of a virtual fieldtrip to Kinlochleven in Scotland to teach undergraduate students geological mapping skills in a structurally complex, polyphase deformed metamorphic terrain. An area of ∼4 km2 of the Highlands was digitally replicated within the game engine Unity and featured 82 outcrops digitized from field data by photogrammetry. Key concepts in the development were: (1) usability on low-specification computers, (2) participant communication within-app, (3) multiscale visualisation of localities, (4) contextualisation of localities within terrain, and (5) a high degree of immersion to replicate the outdoor fieldwork experience. Technology constraints, however, required compromise between the number of localities used and their resolution. Evaluation and assessment data suggests the virtual fieldtrip was effective in delivering the key learning objectives of the course. Student behavioural indicators, furthermore, suggest that the immersive strategy successfully produced a high degree of engagement with the activity. A major limitation of the virtual fieldtrip was in the development of skills requiring spatial visualisation, in particular, the spatial association of features across multiple scales. The virtual fieldtrip had benefits for inclusivity, making fieldwork more accessible than its outdoor equivalent. However, a digital divide was observed to exist between groups depending on experience with gaming and virtual worlds. In addition, neurodiverse group of students required adaptations to assist with spatial awareness in virtual environments. The data obtained suggests that virtual fieldtrips cannot fully replace their outdoor equivalents, however, they are valuable in supplementing and supporting outdoor fieldtrips, in particular by increasing inclusivity and enabling field time to be used optimally.